2017
DOI: 10.1155/2017/3518103
|View full text |Cite
|
Sign up to set email alerts
|

A Single Perioperative Injection of Dexamethasone Decreases Nausea, Vomiting, and Pain after Laparoscopic Donor Nephrectomy

Abstract: Background. A single dose of perioperative dexamethasone (8–10 mg) reportedly decreases postoperative nausea, vomiting, and pain but has not been widely used in laparoscopic donor nephrectomy (LDN). Methods. We performed a retrospective cohort study of living donors who underwent LDN between 2013 and 2015. Donors who received a lower dose (4–6 mg)  (n = 70) or a higher dose (8–14 mg) of dexamethasone (n = 100) were compared with 111 donors who did not receive dexamethasone (control). Outcomes and incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…[27] In a previous study, Yamanaga et al reported an incidence of PONV higher than 60% in patients undergoing laparoscopic donor nephrectomy. [28] Therefore, an opioid-based PCA regimen with a lower risk of PONV is particularly important among high-risk laparoscopic surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…[27] In a previous study, Yamanaga et al reported an incidence of PONV higher than 60% in patients undergoing laparoscopic donor nephrectomy. [28] Therefore, an opioid-based PCA regimen with a lower risk of PONV is particularly important among high-risk laparoscopic surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible mechanism for PONV prophylaxis by corticosteroids is opioid-sparing effects because the postoperative use of opioids has been identified as an independent predictor of PONV [ 8 , 21 , 22 ]. Perineural dexamethasone infiltration has been shown to reduce the incidence of PONV in association with a decrease in postoperative opioid consumption consistent with superior pain relief [ 14 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone has been used for many years to reduce the incidence of PONV (5)(6)(7)(8)21) . Currently, it is recommended as a single perioperative injection of 8-14 mg to decrease PONV in the rst 24 h after surgery (22) . It also has analgesic effects, improves respiratory parameters, decreases fatigue, low-cost drug and promotes better recovery (3,19,21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is recommended as a single perioperative injection of 8-14 mg to decrease PONV in the rst 24 h after surgery (22) . It also has analgesic effects, improves respiratory parameters, decreases fatigue, low-cost drug and promotes better recovery (3,19,21,22) . However, PONV prophylaxis with dexamethasone (8 mg) IV increases postoperative blood glucose values in non-diabetic and diabetic patients, irrespective of baseline blood glucose levels (23) .…”
Section: Discussionmentioning
confidence: 99%